Enhancing the production of the fermentable sugars from sugarcane straw: A new approach to applying alkaline and ozonolysis pretreatments - Ortega, Julieth Orduña [UNESP]; Mora Vargas, Jorge Andrés [UNESP]; Metzker, Gustavo [UNESP]; Gomes, Eleni [UNESP]; da Silva, Roberto [UNESP]; Boscolo, Mauricio [UNESP] (Elsevier, 2021)
The present study, sugarcane straw residue (SCS) was submitted to a combination of mild alkaline pretreatment and ozone cycles in a rotary reactor aiming to obtain fermentable sugars. The SCS exposed to short ozone cycles and short reaction times proved to be as efficient as long ozone exposure times usually employed, with no significant variation on the concentration of the fermentable sugars. Also, studies carried out on the ozone concentration, ozone exposure time, reaction time and biomass amount on the ozonolysis process were conducted. The washing processes after alkaline pretreatment and ozonolysis were also studied. During the alkaline pretreatment, approximately 73% of total phenolic compounds (TPC) was generated. After the first wash 79% of the TPC was washed away and 95% was removed after the second wash. The TPC content in wash solution obtained after ozonolysis is about 2.3% of the TPC generated with the alkaline pretreatment. For the enzymatic hydrolysate 0.20 g L−1 of TPC was obtained, a low value compared to similar studies. The inhibitor detected in the highest concentration was acetic acid for all solutions, except for ozonolysis where fumaric acid predominated. Hydroxymethylfurfural (HMF) and furfural were detected in amounts of less than 10 mg L−1.
Keywords: Alkaline pretreatment; Bioenergy; Fermentable sugars; Ozonolysis; Sugarcane straw